Relationship Between Anxiety Levels With Hypertension Events In Elderly In Public Healt Ujung Loe - Nirmawati; Adam; Andi Suswani (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
Hypertension is an increase in blood pressure> 140/90 mmHg. with increasing age, almost all people experience hypertension. Cases of hypertension that occur at the health center at the end of the street are 78 people who suffer and among them 52 elderly people who suffer from hypertension. The purpose of this study was to determine the relationship between the level of anxiety with the incidence of hypertension in the elderly at Puskesmas Ujung Loe in 2018. Research methods: This study used an analytic observational design with a